Предмет:
МатематикаАвтор:
анонимb^2 / (2ab - b^2) : (2ab / (a^2 - 4b^2) - b / (a + 2b)) = (b^2 / b * (2a - b)) : (2ab / (a - 2b) * (a + 2b) - b / (a + 2b)) = b / (2a - b) : (2ab - ab + 2b^2) / (a - 2b) * (a + 2b) = b / (2a - b) : (ab + 2b^2) / (a - 2b) * (a + 2b) = b / (2a - b) * (a - 2b) * (a + 2b) / b * (a + 2b) = b * (a - 2b) * (a + 2b) / (2a - b) * b * (a + 2b) = (a - 2b) / (2a - b).
Ответ: (a - 2b) / (2a - b).
Автор:
skippymooneyДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть